Composite negative electrode material and preparation method thereof, negative electrode plate, secondary battery and electric device

By setting a silicon material layer on the surface of the carbon fiber composite material of lithium ion batteries, combined with the fast ion conductor, the capacity and cycle stability of lithium -ion batteries are solved, and higher performance and cycle stability are achieved.

CN119381415AActive Publication Date: 2025-01-28CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310932228.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-27
Publication Date
2025-01-28
Estimated Expiration
2043-07-27

AI Technical Summary

Technical Problem

The graphite negative electrode material of existing lithium-ion batteries has a lower theoretical specific capacity and cannot meet the needs of high capacity and high power. At the same time, the volume of silicon material changes greatly during the lithium-ion embedding and disengagement process, resulting in electrode structure failure and deterioration of cycling performance.

Method used

Provide a composite negative material, including carbon fiber composite material and silicon material layer on its surface. The carbon fiber composite material has a three -dimensional fiber network structure and loaded fast ion conductors to improve the transmission path and conductivity of lithium ions.

Benefits of technology

By shortening the transmission path of lithium ions and increasing the ionic conductivity of the negative electrode, the cycle stability and magnification performance of the battery at a high power and fast charging conditions are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381415A_ABST
    Figure CN119381415A_ABST
Patent Text Reader

Abstract

The invention relates to a composite negative electrode material and a preparation method thereof, a negative electrode plate, a secondary battery and an electric device. The composite negative electrode material comprises a carbon fiber composite material and a silicon material layer arranged on at least part of the surface of the carbon fiber composite material, and the carbon fiber composite material comprises carbon fibers with a three-dimensional fiber network structure and a fast ion conductor compounded on the carbon fibers. The composite negative electrode material can reduce the expansion force of the battery, improve the ionic conductivity of the negative electrode, and prolong the cycle life of the lithium ion battery under high-rate rapid charge and discharge conditions, thereby obtaining the lithium ion battery with excellent comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite negative electrode material and a preparation method thereof, a negative electrode sheet, a secondary battery and an electrical device. Background Art

[0002] Secondary batteries are widely used in various consumer electronic products and electric vehicles due to their outstanding features such as light weight, no pollution, and no memory effect. Lithium-ion batteries have achieved a dominant position in many areas of the battery market due to their advantages such as high energy density, long life, and no memory effect. As lithium-ion batteries have made great progress, especially with the widespread application of lithium-ion batteries in new energy electric vehicles, higher requirements have been placed on the energy density and fast charging capabilities of lithium-ion batteries. However, the theoretical specific capacity of commercial graphite anode materials is only 372mAh / g, which is relatively low and can no longer meet the growing demand for high capacity and high power. Therefore, finding higher capacity electrode materials to replace commercial graphite anodes has become an important exploration direction for lithium-ion battery anode research.

[0003] Silicon is the material with the highest known lithium insertion capacity (3579-4200mAh / g). It also has the advantages of low discharge potential and abundant natural reserves, making it the most promising negative electrode material for lithium-ion batteries to replace graphite. However, during the process of lithium ion insertion and extraction, silicon materials will have a volume change of up to 300%, which will lead to problems such as electrode structure destruction, electrical connection failure, and continuous consumption of active materials, and ultimately lead to the destruction of battery performance, such as deterioration of cycle performance. Improving the volume change problem of silicon during battery cycles through nano-scaling or silicon-carbon composites is currently a relatively common method, but the improvement effect is not ideal, especially the cycle stability problem under high-rate rapid charge and discharge conditions cannot be effectively solved. Therefore, existing negative electrode materials still need to be improved. Summary of the invention

[0004] Based on this, it is necessary to provide a composite negative electrode material and a preparation method thereof, a negative electrode plate, a secondary battery and an electrical device to improve the cycle stability of the battery under high-rate rapid charge and discharge conditions.

[0005] In order to achieve the above-mentioned objectives, the first aspect of the present application provides a composite negative electrode material, including a carbon fiber composite material and a silicon material layer arranged on at least a portion of the surface of the carbon fiber composite material, wherein the carbon fiber composite material includes carbon fibers having a three-dimensional fiber network structure and a fast ion conductor composited on the carbon fibers.

[0006] In some embodiments, the fast ion conductor includes one or more of a perovskite fast ion conductor, a garnet fast ion conductor, and a NASICON fast ion conductor;

[0007] Optionally, the fast ion conductor includes a perovskite fast ion conductor, a garnet fast ion conductor and a NASICON fast ion conductor;

[0008] Further optionally, the mass ratio of the perovskite type fast ion conductor, the garnet type fast ion conductor and the NASICON type fast ion conductor is (1-2):(1-2):1.

[0009] In some embodiments, the chemical formula of the perovskite fast ion conductor is Li 3x1 La 2 / 3- x1 M y1 TiD z1 O3, where M includes Ba 2+ and Sr 2+ One or more of, D includes Al 3+ and Zr 4+ One or more of 0.04≤x1≤0.167, 0≤y1≤1, 0≤z1≤1, optional Li 0.33 La 0.56 TiO3; and / or,

[0010] The chemical formula of the garnet-type fast ion conductor is Li 7-y2 La 3-x2 A x2 Zr 2-y2 B y2 O 12 , wherein 0≤x2≤3, 0≤y2≤2, A includes one or more of Y, Nd and Gd, B includes one or more of Nb and Ta, and can be selected from Li7La3Zr2O 12 and / or,

[0011] The chemical formula of the NASICON type fast ion conductor is Li 1+x3 M'2(PO4)3, M' includes one or more of Al, Ti, Ge, Hf, 0.1≤x3≤0.5, and can be Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0012] In some of the embodiments, the fast ion conductor is ceramic particles, and the average volume particle size Dv50 of the ceramic particles is 10 nm to 70 nm, and can be optionally 20 nm to 50 nm.

[0013] In some embodiments, the carbon fiber composite material satisfies at least one of the following characteristics (1)-(3):

[0014] (1) The average diameter of the carbon fibers in the carbon fiber composite material is 0.1 μm to 1 μm;

[0015] (2) The porosity of the carbon fiber composite material is 20% to 70%;

[0016] (3) The mass ratio of carbon fiber to fast ion conductor in the carbon fiber composite material is (1-19):1, and can be optionally (1.2-9):1.

[0017] In some embodiments, the silicon material layer satisfies at least one of the following characteristics (4)-(5):

[0018] (4) The thickness of the silicon material layer is 5 nm to 100 nm, and can be optionally 10 nm to 80 nm;

[0019] (5) The average volume particle size Dv50 of the silicon material in the silicon material layer is 3 nm to 10 nm.

[0020] In some embodiments, the composite negative electrode material satisfies at least one of the following characteristics (6)-(10):

[0021] (6) The average volume particle size Dv50 of the composite negative electrode material is 5 μm to 20 μm;

[0022] (7) The specific surface area of ​​the composite negative electrode material is 1 m 2 / g~20m 2 / g;

[0023] (8) Based on the mass of the composite negative electrode material, the mass content of the silicon material in the silicon material layer is 1% to 70%;

[0024] (9) Based on the mass of the composite negative electrode material, the mass content of the fast ion conductor is 10% to 50%;

[0025] (10) Based on the mass of the composite negative electrode material, the mass content of the carbon fiber is 5% to 30%.

[0026] The second aspect of the present application provides a method for preparing the composite negative electrode material, comprising:

[0027] Providing the carbon fiber composite material;

[0028] The silicon material layer is formed on the carbon fiber composite material.

[0029] In some embodiments, the method for preparing the carbon fiber composite material comprises the following steps:

[0030] S11, mixing an organic polymer, a fast ion conductor, a complexing agent and a solvent to obtain a mixed solution;

[0031] S12, heat-treating the mixed solution to obtain a fiber prefabricated solution;

[0032] S13, preparing the fiber prefabricated liquid through an electrostatic spinning process to obtain a fiber structure material;

[0033] S14, sintering the fiber structure material to obtain a carbon fiber composite material.

[0034] In some embodiments, the organic polymer includes one or more of polyvinyl alcohol, polyacrylonitrile, polyethylene oxide, polyphenylene ether, polyethylene glycol, polymethyl methacrylate and polyvinylidene fluoride hexafluoropropylene.

[0035] In some embodiments, the preparation method satisfies at least one of the following characteristics (11)-(12):

[0036] (11) The concentration of the organic polymer in the mixed solution is 0.01 to 0.20 Kg / L, and can be 0.08 to 0.18 Kg / L; and / or,

[0037] (12) The concentration of the fast ion conductor is 0.01 to 0.20 Kg / L, and can be optionally 0.08 to 0.15 Kg / L.

[0038] In some of the embodiments, the method for forming the silicon material layer includes at least one of chemical vapor deposition, physical vapor deposition, plasma spraying and screen printing, and chemical vapor deposition can be selected.

[0039] The third aspect of the present application provides a negative electrode plate, comprising the composite negative electrode material of the first aspect of the present application or the composite negative electrode material prepared by the method of the second aspect of the present application.

[0040] The fourth aspect of the present application provides a secondary battery, comprising the negative electrode plate of the third aspect of the present application.

[0041] A fifth aspect of the present application provides an electrical device, comprising the secondary battery of the fourth aspect of the present application.

[0042] Effects of the Invention

[0043] The composite negative electrode material provided in the present application includes a carbon fiber composite material and a silicon material layer arranged on the surface of the carbon fiber composite material, wherein the carbon fiber composite material is based on carbon fiber, the carbon fiber has a three-dimensional fiber network structure, and a fast ion conductor is loaded on the carbon fiber, and the fast ion conductor has the ability to quickly transmit lithium ions. The carbon fiber composite material thus formed not only has a conductive three-dimensional fiber network structure, but also increases the Li + The transmission path, combined with the silicon material layer, makes Li+ It can be quickly transmitted along the three-dimensional fiber network structure, greatly shortening the transmission path of lithium ions, improving the ionic conductivity of the negative electrode, and then improving the rate performance of the negative electrode, and improving the cycle stability of the battery under high-rate rapid charging and discharging conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is a schematic diagram of a secondary battery according to one embodiment of the present application.

[0045] Figure 2 for Figure 1 An exploded view of a secondary battery according to an embodiment of the present application is shown.

[0046] Figure 3 It is a schematic diagram of a battery module according to one embodiment of the present application.

[0047] Figure 4 A schematic diagram of a battery pack according to an embodiment of the present application.

[0048] Figure 5 for Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.

[0049] Figure 6 A schematic diagram of an electrical device using a secondary battery according to an embodiment of the present application as a power source.

[0050] Description of reference numerals:

[0051] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate; 6 electrical device. DETAILED DESCRIPTION

[0052] Below, the embodiments of the positive electrode active material and its manufacturing method, positive electrode sheet, secondary battery, battery module, battery pack and electrical device of the present application are specifically disclosed with appropriate reference to the drawings. However, there are cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0053] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0054] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0055] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0056] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0057] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0058] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0059] At present, in order to meet market demand, the energy density of secondary batteries represented by lithium-ion batteries is getting higher and higher. With the continuous development of new energy electric vehicles, problems such as mileage anxiety and long charging time have become prominent. In this case, the improvement of the fast charging ability of high-energy-density batteries has become the focus of the development of the next generation of batteries. At the same time, in order to improve the energy density, silicon-based materials have been introduced in the selection of active materials for secondary batteries. The volume of silicon-based materials changes greatly during the cycle of secondary batteries. During high-rate fast charging, the volume of silicon-based materials changes even more, which can exceed 300%, resulting in the collapse of the structure of the negative electrode material. In order to solve the problem of volume change of silicon negative electrode materials, the existing technology focuses on the research of developing suitable carriers. However, based on the increasingly stringent demand for the fast charging ability of batteries, the inventors found that only the carrier to ensure the expansion space of silicon has limited improvement in the high-rate fast charging ability of the negative electrode material, and shortening the lithium ion transmission path can enable the anode to have the ability to quickly transmit lithium ions, thereby greatly improving its fast charging ability. Therefore, it is necessary to construct a negative electrode active material that can provide sufficient space to accommodate the volume change of silicon material and shorten the lithium ion transmission path, so as to solve the problem of cycle stability of high energy density batteries under high-rate rapid charging and discharging conditions.

[0060] Composite negative electrode materials

[0061] To this end, the first aspect of an embodiment of the present application provides a composite negative electrode material, comprising a carbon fiber composite material and a silicon material layer arranged on at least a portion of the surface of the carbon fiber composite material, wherein the carbon fiber composite material comprises carbon fibers having a three-dimensional fiber network structure and a fast ion conductor composited on the carbon fibers.

[0062] In the embodiment of the present application, the composite negative electrode material includes a carbon fiber composite material and a silicon material layer arranged on the surface of the carbon fiber composite material, wherein the carbon fiber composite material is based on carbon fiber, the carbon fiber has a three-dimensional fiber network structure, and a fast ion conductor is composited on the carbon fiber, and the fast ion conductor has the ability to quickly transmit active ions such as lithium ions. The carbon fiber composite material thus formed not only has a conductive three-dimensional fiber network structure, but also increases the Li + The transmission path, combined with the silicon material layer, makes Li +It can be quickly transmitted along the three-dimensional fiber network structure, greatly shortening the transmission path of lithium ions, improving the ionic conductivity of the negative electrode, and then improving the rate performance of the negative electrode, and improving the cycle stability of the battery under high-rate rapid charging and discharging conditions.

[0063] It should be noted that the silicon material layer can be disposed on part of the surface of the carbon fiber composite material, or on the entire surface of the carbon fiber composite material; preferably, the silicon material layer is disposed on the entire surface of the carbon fiber composite material, for example, the silicon material layer covers the three-dimensional fiber network structure skeleton of the carbon fiber composite material, and the three-dimensional fiber network structure skeleton of the carbon fiber composite material is completely covered with the silicon material layer. Furthermore, the surface formed by the silicon material layer can be a continuous surface or a discontinuous surface; preferably, the surface formed by the silicon material layer is a continuous surface.

[0064] It should be further explained that the composite form of the fast ion conductor and the carbon fiber is not particularly limited. Optionally, the fast ion conductor is composited with the carbon fiber in the form of particles, with the carbon fiber serving as the matrix. The fast ion conductor particles can be located on the surface of the carbon fiber or inside the carbon fiber.

[0065] In this application, a fast ion conductor refers to a conductor that has the ionic conductivity of a molten salt or liquid electrolyte in the solid state. Its basic characteristics that distinguish it from a general ion conductor are that it has an ionic conductivity comparable to that of a liquid electrolyte within a certain temperature range and a low ionic conductivity activation energy. The ionic (including vacancy) conductivity of a fast ion conductor can be greater than or equal to 10 -2 Ω -1 cm -1 , the activation energy is less than or equal to 0.5 eV, further, the migration number of ions (including vacancies) is greater than 99%, it is a conductor for ions and an insulator for electrons.

[0066] In some embodiments, the fast ion conductor includes one or more of a perovskite-type fast ion conductor, a garnet-type fast ion conductor, and a NASICON-type fast ion conductor.

[0067] In some preferred embodiments, the fast ion conductor includes a perovskite-type fast ion conductor, a garnet-type fast ion conductor, and a NASICON-type fast ion conductor.

[0068] In some embodiments, the chemical formula of the perovskite fast ion conductor is Li 3x1 La 2 / 3-x1 M y1 TiD z1 O3, where M includes Ba 2+ and Sr 2+ One or more of, D includes Al 3+ and Zr 4+One or more of 0.04≤x1≤0.167, 0≤y1≤1, 0≤z1≤1. Without limitation, specific examples of perovskite-type fast ion conductors include Li 0.33 La 0.56 TiO3.

[0069] In some embodiments, the garnet-type fast ion conductor has the formula Li 7-y2 La 3-x2 A x2 Zr 2-y2 B y2 O 12 , wherein 0≤x2≤3, 0≤y2≤2, A includes one or more of Y, Nd, and Gd, and B includes one or more of Nb and Ta. Without limitation, specific examples of garnet-type fast ion conductors include Li7La3Zr2O 12 .

[0070] In some embodiments, the NASICON-type fast ion conductor has the formula Li 1+x3 M'2(PO4)3, M' includes one or more of Al, Ti, Ge, Hf, 0.1≤x3≤0.5. Without limitation, specific examples of NASICON type fast ion conductors include Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0071] In some optional embodiments, the fast ion conductor includes a perovskite fast ion conductor, a garnet fast ion conductor and a NASICON fast ion conductor. Without being limited to any theory, the synergistic cooperation of the three types of fast ion conductors can further improve the lithium ion transmission rate of the composite negative electrode material and further improve the ionic conductivity of the negative electrode. Optionally, the mass ratio of the perovskite fast ion conductor, the garnet fast ion conductor and the NASICON fast ion conductor is (1-2): (1-2): 1, which can be understood to be 1:1:1, 1:2:1, 2:1:1, 2:2:1, etc., without specific limitation. The mass ratio of the perovskite fast ion conductor, the garnet fast ion conductor and the NASICON fast ion conductor can have a better synergistic effect within the above range.

[0072] In some embodiments, the fast ion conductor comprises Li 0.33 La 0.56 TiO3、Li7La3Zr2O 12 and Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0073] In some embodiments, the fast ion conductor is a ceramic particle, and the average volume particle size Dv50 of the ceramic particle is 10nm to 70nm, for example, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm and any value therebetween. When the average volume particle size Dv50 of the fast ion conductor ceramic particles is within the above range, the distribution uniformity and ion transmission distance are better, which can further improve its fast ion transmission performance. Optionally, the average volume particle size Dv50 of the fast ion conductor ceramic particles is 20nm to 50nm.

[0074] In some embodiments, the average diameter of the carbon fiber is 0.1 μm to 1 μm, such as 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm and any value therebetween. When the average diameter of the carbon fiber is within the above range, the composite negative electrode material has better mechanical properties and conductive properties. Optionally, the average diameter of the carbon fiber is 0.1 μm to 0.5 μm.

[0075] The average diameter of the carbon fibers is a well-known meaning in the art and can be measured using instruments and methods known in the art, such as transmission electron microscopy.

[0076] In some embodiments, the porosity of the carbon fiber composite material is 20% to 70%, such as 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% and any value therebetween. The porosity of the carbon fiber composite material is within the above range, has a better specific surface area and structural stability, can further increase the deposition amount of silicon, and has a higher energy density. Optionally, the porosity of the carbon fiber composite material is 30% to 50%.

[0077] The carbon fiber composite material is a mixed ion-electron conductor. In some embodiments, the mass ratio of carbon fiber to fast ion conductor in the carbon fiber composite material is (1-19):1, such as 2:1, 4:1, 6:1, 8:1, 9:1, 10:1, 12:1, 14:1, 16:1, 18:1 and any ratio therebetween. When the mass ratio of fast ion conductor to carbon fiber in the carbon fiber composite material is within this range, the composite negative electrode material has better electrical conductivity and ionic conductivity, which can further improve the cycle performance of the battery at high rates. Optionally, the mass ratio of carbon fiber to fast ion conductor in the carbon fiber composite material is (1.2-9):1.

[0078] In some embodiments, the thickness of the silicon material layer is 5nm to 100nm, such as 10nm, 15nm, 20nm, 25nm, 30nm, 35nm, 40nm, 45nm, 50nm, 55nm, 60nm, 65nm, 70nm, 75nm, 80nm, 85nm, 90nm, 95nm and any value therebetween. When the thickness of the silicon material layer is within this range, the negative electrode active material has a better silicon content, which can improve its gram capacity, as well as better conductivity and cycle performance. Optionally, the thickness of the silicon material layer is 10nm to 80nm.

[0079] In some embodiments, the volume average particle size Dv50 of the silicon material in the silicon material layer is 2nm to 20nm, such as 3nm, 5nm, 7nm, 9nm, 11nm, 13nm, 15nm, 17nm, 19nm and any value therebetween. Optionally, the volume average particle size Dv50 of the silicon material in the silicon material layer is 3nm to 10nm.

[0080] The volume average particle size Dv50 of the silicon material in the silicon material layer is well known in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be tested by instruments and methods well known in the art. For example, it can be conveniently tested by using a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.

[0081] In some embodiments, the volume average particle size Dv50 of the composite negative electrode material is 3 μm to 30 μm, for example, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm and any value therebetween. Optionally, the volume average particle size Dv50 of the composite negative electrode material is 5 μm to 20 μm.

[0082] The volume average particle size Dv50 of the composite negative electrode material is well known in the art, which indicates the particle size corresponding to when the cumulative volume distribution percentage of the material reaches 50%, and can be tested by instruments and methods well known in the art. For example, it can be conveniently tested by a laser particle size analyzer with reference to GB / T 19077-2016 particle size distribution laser diffraction method, such as the Mastersizer 2000E laser particle size analyzer of Malvern Instruments Ltd., UK.

[0083] In some embodiments, the specific surface area of ​​the composite negative electrode material is 1 m 2 / g~20m 2 / g, for example 2m 2 / g, 4m 2 / g, 6m 2 / g, 8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 18m 2 / g and any value therebetween. Optionally, the specific surface area of ​​the composite negative electrode material is 2m 2 / g~15m 2 / g.

[0084] In some embodiments, the mass content of silicon is 1% to 70%, based on the mass of the composite negative electrode material, for example 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65% and any value therebetween.

[0085] In some embodiments, the mass content of the fast ion conductor is 10% to 50%, based on the mass of the composite negative electrode material, for example, 12%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32%, 35%, 38%, 40%, 42%, 45%, 48% and any value therebetween.

[0086] In some embodiments, based on the mass of the composite negative electrode material, the mass content of the carbon fiber is 5% to 30%, for example 6%, 8%, 10%, 12%, 15%, 18%, 20%, 22%, 25%, 28% and any value therebetween.

[0087] In the present application, a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) can be used to prepare the cross-section of the composite negative electrode material particles, which passes through the core of the composite negative electrode material particles; then, EDX or EDS elemental analysis is combined with TEM or SEM (such as the X-Max EDS of the Oxford Instruments Group in the UK combined with the Sigma-02-33 SEM of ZEISS in Germany) surface scanning test to obtain the element distribution map in the cross-section; combined with methods known in the art, the structure, composition and characteristics and content of each component of the composite negative electrode material can be further obtained.

[0088] For example, the mass content of silicon, the mass content of fast ion conductors and carbon fibers, the cross section of the negative electrode active material particles is prepared using a cross section polisher (such as the IB-09010CP argon ion cross section polisher of JEOL), which passes through the core of the negative electrode active material particles; then the element distribution map in the cross section is obtained by EDX or EDS element analysis combined with TEM or SEM (such as the X-Max EDS of the Oxford Instruments Group in the UK combined with the Sigma-02-33 SEM of ZEISS in Germany) surface scanning test; in an area within the cross section, the Si content or the specific element content or carbon content of the fast ion conductor in the area can be obtained by integrating the silicon element distribution or the specific element distribution of the fast ion conductor or the carbon element distribution. In order to improve the accuracy of the test, multiple areas (for example, 10) can be counted and the average value is taken as the test result.

[0089] For another example, the thickness of the silicon material layer can be measured by using a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) to prepare the cross section of the negative electrode active material particles, which passes through the core of the negative electrode active material particles; then, the element distribution map in the cross section is obtained by EDX or EDS element analysis combined with TEM or SEM (such as the X-Max EDS of the Oxford Instruments Group in the UK combined with the Sigma-02-33 SEM of ZEISS in Germany) surface scanning test; the thickness of the silicon material layer is obtained according to the element distribution of the cross section. More precisely, the thickness of the silicon material layer at multiple (more than 3, such as 8, 10, 12, etc.) different positions on the cross section can be tested, and the average value is recorded as the thickness of the silicon material layer.

[0090] Preparation method of composite negative electrode material

[0091] A second aspect of the present application provides a method for preparing a negative electrode material, comprising:

[0092] S10, providing carbon fiber composite materials; and

[0093] S20, forming a silicon material layer on the carbon fiber composite material.

[0094] In some embodiments, the method for preparing the carbon fiber composite material comprises the following steps:

[0095] S11, mixing an organic polymer, a fast ion conductor, a complexing agent and a solvent to obtain a mixed solution;

[0096] S12, heat-treating the mixed solution to obtain a fiber prefabricated solution;

[0097] S13, preparing a fiber structure material by electrospinning the fiber prefabricated liquid;

[0098] S14, sintering the fiber structural material to obtain a carbon fiber composite material.

[0099] Optionally, in step S11, the organic polymer includes one or more of polyvinyl alcohol, polyacrylonitrile, polyethylene oxide, polyphenylene ether, polyethylene glycol, polymethyl methacrylate, and polyvinylidene fluoride hexafluoropropylene.

[0100] Optionally, in step S11, the fast ion conductor includes one or more of any of the fast ion conductors mentioned above. In some embodiments, the fast ion conductor includes Li 0.33 La 0.56 TiO3、Li7La3Zr2O 12 and Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0101] Optionally, in step S11, the complexing agent includes one or more of citric acid, malic acid, malonic acid, succinic acid, succinic acid, glycolic acid, aminoacetic acid, lactic acid, tartaric acid, and EDTA (Chinese name: ethylenediaminetetraacetic acid).

[0102] Optionally, in step S11, the solvent is water.

[0103] Optionally, the temperature of the heat treatment in step S12 is 500° C. to 1000° C., and the time of the heat treatment is 1 h to 5 h.

[0104] In some embodiments, the concentration of the organic polymer in the mixed solution is 0.01-0.20 Kg / L, and can be optionally 0.08-0.18 Kg / L.

[0105] In some embodiments, the concentration of the fast ion conductor is 0.01 to 0.20 Kg / L, and optionally 0.08 to 0.15 Kg / L.

[0106] In some embodiments, the silicon material layer is formed by chemical vapor deposition, physical vapor deposition, plasma spraying or screen printing, and chemical vapor deposition may be selected.

[0107] Negative electrode

[0108] The third aspect of the embodiment of the present application provides a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, and the negative electrode active material includes the composite negative electrode material of the first aspect of the present application or the composite negative electrode material prepared by the method of the second aspect of the present application. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode active material layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.

[0109] The negative electrode plate includes the composite negative electrode material provided in the present application, wherein the composite negative electrode material can improve the cycle stability of the battery under high-rate rapid charging and discharging conditions.

[0110] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material on a polymer material substrate. Among them, the metal material includes but is not limited to copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc., and the polymer material substrate includes but is not limited to polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and other substrates.

[0111] In some embodiments, the negative electrode active material does not exclude other negative electrode active materials other than the composite negative electrode material provided in the present application. Other negative electrode active materials may adopt negative electrode active materials for secondary batteries known in the art. As an example, other negative electrode active materials may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, other silicon-based materials, tin-based materials, lithium titanate, etc. The other silicon-based materials may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more. The weight ratio of the negative electrode active material in the negative electrode active material layer is 70-100% by weight, based on the total weight of the negative electrode active material layer.

[0112] In some embodiments, the negative electrode active material layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS). The weight ratio of the binder in the negative electrode active material layer is 0-30% by weight, based on the total weight of the negative electrode active material layer.

[0113] In some embodiments, the negative electrode active material layer may further optionally include a conductive agent. The conductive agent may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the negative electrode active material layer is 0-20% by weight, based on the total weight of the negative electrode active material layer.

[0114] In some embodiments, the negative electrode active material layer may further include other additives, such as a thickener (such as sodium carboxymethyl cellulose (CMC-Na)), etc. The weight ratio of the other additives in the negative electrode active material layer is 0-15% by weight, based on the total weight of the negative electrode active material layer.

[0115] In some embodiments, the negative electrode sheet can be prepared by the following method: the above components for preparing the negative electrode sheet, such as the negative electrode active material provided in the present application, optional other negative electrode active materials, optional binder, optional conductive agent and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The solid content of the negative electrode slurry can be 30-70wt%, the viscosity at room temperature can be adjusted to 2000-10000mPa·s, and the compaction density of the negative electrode sheet can be 1.2-2.0g / m 3 , the thickness of the negative electrode active material layer can be 34 μm to 143 μm.

[0116] The thickness T of the negative electrode active material layer can be measured by using a micrometer, for example, a Mitutoyo 293-100 micrometer with an accuracy of 0.1 μm. It should be noted that the thickness of the negative electrode active material layer described in this application refers to the thickness of the negative electrode active material layer in the negative electrode sheet after cold pressing and used to assemble the battery.

[0117] The negative electrode sheet of the present application does not exclude other additional functional layers in addition to the negative electrode active material layer. For example, in some embodiments, the negative electrode sheet of the present application also includes a conductive primer layer (for example, composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode active material layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode sheet of the present application also includes a protective layer covering the surface of the negative electrode active material layer.

[0118] In addition, the secondary battery, battery module, battery pack, and electric device of the present application will be described below with reference to the drawings as appropriate.

[0119] In one embodiment of the present application, a secondary battery is provided.

[0120] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0121] Positive electrode

[0122] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer arranged on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode active material of the first aspect of the present application.

[0123] As an example, the positive electrode current collector has two surfaces facing each other in its thickness direction, and the positive electrode active material layer is disposed on any one or both of the two facing surfaces of the positive electrode current collector.

[0124] In some of the embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base and a metal layer formed on at least one surface of the polymer material base. The composite current collector may be formed by forming a metal material (aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0125] In some of the embodiments, the positive electrode active material may adopt the positive electrode active material for batteries known in the art. As an example, the positive electrode active material may include at least one of the following materials: lithium-containing phosphates with an olivine structure, lithium transition metal oxides and their respective modified compounds. However, the present application is not limited to these materials, and other traditional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Among them, examples of lithium transition metal oxides may include, but are not limited to, lithium cobalt oxide (such as LiCoO2), lithium nickel oxide (such as LiNiO2), lithium manganese oxide (such as LiMnO2, LiMn2O4), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (such as LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 (also referred to as NCM 333 )、LiNi 0.5 Co 0.2 Mn 0.3 O2 (also referred to as NCM 523)、LiNi 0.5 Co 0.25 Mn 0.25 O2 (also referred to as NCM 211 )、LiNi 0.6 Co 0.2 Mn 0.2 O2 (also referred to as NCM 622 )、LiNi 0.8 Co 0.1 Mn 0.1 O2 (also referred to as NCM 811 ), lithium nickel cobalt aluminum oxide (such as LiNi 0.85 Co 0.15 Al 0.05 O2) and its modified compounds, etc. Examples of lithium-containing phosphates with an olivine structure may include, but are not limited to, lithium iron phosphate (such as LiFePO4 (also referred to as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, and a composite material of lithium iron manganese phosphate and carbon. The weight ratio of the positive electrode active material in the positive electrode active material layer is 80-100% by weight, based on the total weight of the positive electrode active material layer.

[0126] In some embodiments, the positive electrode active material layer may also optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and fluorine-containing acrylate resin. The weight ratio of the binder in the positive electrode active material layer is 0-20% by weight, based on the total weight of the positive electrode active material layer.

[0127] In some embodiments, the positive electrode active material layer may further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. The weight ratio of the conductive agent in the positive electrode active material layer is 0-20 weight %, based on the total weight of the positive electrode active material layer.

[0128] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The positive electrode slurry has a solid content of 40-80wt%, the viscosity at room temperature is adjusted to 5000-25000mPa·s, and the compacted density of the positive electrode sheet is 3.0-3.6g / cm 3 , optional: 3.3-3.5g / cm 3 The thickness of the positive electrode active material layer is 51-152 μm.

[0129] The thickness T of the positive electrode active material layer can be measured by using a micrometer, for example, a Mitutoyo 293-100 micrometer with an accuracy of 0.1 μm. It should be noted that the thickness of the positive electrode active material layer described in this application refers to the thickness of the positive electrode active material layer in the positive electrode sheet after cold pressing and used to assemble the battery.

[0130] Electrolytes

[0131] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.

[0132] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.

[0133] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate and lithium tetrafluorooxalatophosphate. The concentration of the electrolyte salt is generally 0.5-5 mol / L.

[0134] In some of the embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.

[0135] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0136] Isolation film

[0137] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.

[0138] In some embodiments, the material of the isolation membrane can be selected from at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular limitation.

[0139] In some of the embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly by a winding process or a lamination process.

[0140] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.

[0141] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, and as the plastic, polypropylene, polybutylene terephthalate, and polybutylene succinate can be listed.

[0142] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square or any other shape. Figure 1 The secondary battery 5 is a square structure as an example.

[0143] In some of these embodiments, reference Figure 2 , the outer package may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. ​​The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.

[0144] In some of the embodiments, the secondary batteries may be assembled into a battery module. The number of the secondary batteries contained in the battery module may be one or more, and the specific number may be selected by those skilled in the art according to the application and capacity of the battery module.

[0145] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of secondary batteries 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of secondary batteries 5 may be fixed by fasteners.

[0146] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.

[0147] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. The specific number may be selected by those skilled in the art according to the application and capacity of the battery pack.

[0148] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.

[0149] In addition, the present application also provides an electrical device, which includes at least one of the secondary batteries, battery modules, or battery packs provided in the present application. The secondary batteries, battery modules, or battery packs can be used as power sources for electrical devices, and can also be used as energy storage units for electrical devices. Electrical devices may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited to these. Among them, mobile devices may be, for example, mobile phones, laptop computers, etc.; electric vehicles may be, for example, pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc., but are not limited to these.

[0150] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.

[0151] Figure 6The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of secondary batteries, a battery pack or a battery module can be used.

[0152] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a secondary battery may be used as a power source.

[0153] Example

[0154] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0155] The English abbreviations involved below are explained as follows:

[0156] LLTO stands for Li 0.33 La 0.56 TiO3;

[0157] LLZO stands for Li7La3Zr2O 12 ;

[0158] LATP stands for Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

[0159] 1. Preparation Example

[0160] Preparation Example 1

[0161] 1. Add LLZO, LLTO and LATP ceramic nanoparticles in a mass ratio of 2:2:1 to a polyvinyl alcohol aqueous solution with a concentration of 0.12 Kg / L. The concentration of the ceramic nanoparticles in the solution is 0.12 Kg / L. Add citric acid as a complexing agent in an amount equivalent to the ceramic nanoparticles. Stir for 5 hours in a 95°C water bath to obtain a transparent and uniform spinning solution.

[0162] 2. The above solution was used for electrospinning to obtain a three-dimensional fiber network structure material, wherein the spinning voltage was 12 kV, the injection speed of the syringe needle was 0.4 ml / h, the distance between the syringe needle and the aluminum foil receiver was 15 cm, and the spinning time was 3 h.

[0163] 3. The three-dimensional fiber network structure material is placed in a tubular furnace and calcined in an Ar inert atmosphere at 700° C. for 2 h to obtain a carbon fiber composite material.

[0164] 4. Place the above carbon fiber composite material in a tubular furnace to deposit a nano-silicon material layer, pass Ar inert gas at 900°C for 2 hours, the reaction gas source is SiH4 and C2H2 with a volume ratio of 2:1, the flow rate is 50mL / min, the deposition temperature is 900°C, and the deposition time is 30min, to obtain a three-dimensional fiber network material with amorphous silicon deposition, which is the negative electrode active material.

[0165] According to SEM scanning electron microscopy testing, the composite negative electrode material has a three-dimensional fiber network structure and a three-dimensional network skeleton.

[0166] Preparation Examples 2 to 30

[0167] The preparation methods of Preparation Examples 2 to 30 are similar to Preparation Example 1. The difference is that the composite negative electrode material and the related parameters in the preparation process are adjusted. The specific parameters are shown in the following Table 1. Among them, "-" indicates that the corresponding parameter does not exist.

[0168] Preparation Comparative Example 1

[0169] The preparation method of Comparative Example 1 is different from that of Example 1 in that the addition of LLZO, LLTO and LATP ceramic nanoparticles is omitted in step 1, that is, the spinning solution is only a polyvinyl alcohol aqueous solution and does not include LLZO, LLTO and LATP ceramic nanoparticles.

[0170] 2. Application Examples

[0171] Example 1

[0172] 1) Preparation of positive electrode

[0173] The cathode active material ternary material nickel cobalt manganese (NCM811), conductive carbon black SP and binder PVDF were dispersed in the solvent NMP according to a weight ratio of 97:2:1 and mixed evenly to obtain a cathode slurry; the cathode slurry was evenly coated on the cathode current collector aluminum foil, and then dried, cold pressed, die-cut and striped to obtain a cathode electrode sheet, and the coating amount per unit area was 0.27g / 1540.25mm 2 .

[0174] 2) Preparation of negative electrode sheet

[0175] The composite negative electrode material of Example 1, conductive carbon, thickener sodium hydroxymethyl cellulose (CMC), and binder styrene butadiene rubber (SBR) were mixed in a weight ratio of 96:2:1:1, and deionized water was added to obtain a negative electrode slurry under the action of a vacuum mixer; the negative electrode slurry was evenly coated on a copper foil; the copper foil was dried at room temperature and then transferred to an oven at 85°C for drying, and then cold pressed and cut to obtain a negative electrode sheet, and the coating amount per unit area was 0.17 g / 1540.25 mm 2 .

[0176] 3) Isolation film

[0177] A 12 μm thick porous isolation membrane was selected.

[0178] The preparation of the porous isolation membrane includes: using a polyethylene microporous film as a porous isolation membrane substrate, mixing inorganic alumina powder, polyvinylpyrrolidone, and acetone solvent in a weight ratio of 3:1.5:5.5 to form a slurry, coating it on one side of the substrate, and drying it to obtain a porous isolation membrane.

[0179] 4) Preparation of electrolyte

[0180] The organic solvent is a mixed liquid containing ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate, wherein the volume ratio of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate is 1:2:1. In an argon atmosphere glove box with a water content of <10ppm, fully dried lithium salt LiPF6 is dissolved in the organic solvent and mixed evenly to obtain an electrolyte. The concentration of the lithium salt is 1 mol / L.

[0181] 5) Preparation of batteries

[0182] The positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrodes to play a role of isolation, and then wound into a square bare battery cell, loaded with aluminum plastic film, and then baked at 80°C to remove water, 320g of the corresponding electrolyte is injected, and sealed. After standing, hot and cold pressing, formation, clamping, and capacity division, a finished battery with a capacity of 180Ah is obtained. The battery is charged for the first time with N / P = 1.05. N / P = negative electrode gram capacity * negative electrode active material mass / positive electrode gram capacity * positive electrode active material mass

[0183] The secondary batteries of Examples 2 to 30 and the secondary battery of Comparative Example 1 were prepared in a similar manner to the secondary battery of Example 1, but the composite negative electrode materials of the corresponding preparation examples were used.

[0184] 3. Test Method

[0185] 1. Specific surface area and porosity test

[0186] The specific surface area and pore size distribution of the composite negative electrode materials, carbon fiber composite materials and other materials in the embodiments and comparative examples were tested using a specific surface area analyzer (TristarII 3020M) by nitrogen adsorption / desorption method. The specific test was carried out in accordance with the national standard GB / T 19587-2017.

[0187] 2. Particle size distribution test

[0188] The particle size distribution of the negative electrode active material and the silicon material of the silicon material layer in the embodiment and the comparative example was tested using a Malvern particle size tester to obtain the average volume particle size Dv50 of the composite negative electrode material, the silicon material of the silicon material layer, and the fast ion conductor. The specific test was carried out in accordance with the national standard GB / T19077-2016.

[0189] 3. Silicon material layer thickness

[0190] A cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) is used to prepare the cross-section of the negative electrode active material particles, which passes through the core of the negative electrode active material particles; then the element distribution map in the cross-section is obtained by surface scanning test using the X-Max EDS of the Oxford Instruments Group of the United Kingdom combined with the Sigma-02-33 SEM of the ZEISS of Germany, and the thickness of the silicon material layer is tested according to the element distribution of the cross-section. The thickness values ​​of the silicon material layer at three different positions on the cross-section are taken, and the average value is recorded as the thickness of the silicon material layer.

[0191] 4. Test of the mass content of silicon in the negative electrode active material, the mass content of the fast ion conductor and the mass content of the carbon fiber

[0192] A cross-section polisher (such as the IB-09010CP argon ion cross-section polisher of JEOL) is used to prepare the cross-section of the negative electrode active material particles, which passes through the core of the negative electrode active material particles; then the element distribution map in the cross-section is obtained by surface scanning test using the X-Max EDS of the Oxford Instruments Group of the United Kingdom combined with the Sigma-02-33 SEM of the German ZEISS. In a region within the cross-section, the Si content in the region or the specific element content or carbon content of the three-dimensional network material is obtained by integrating the silicon element distribution or the specific element distribution (such as Ti) of the MXene material or the carbon element distribution. A total of 10 regions were counted in the test, and the average value was taken as the test result.

[0193] 5. Negative electrode ion conductivity test

[0194] The AC impedance method is used to characterize the negative electrode ion conductivity. The negative electrode material is placed between two stainless steel gaskets and the AC impedance method is used to test the frequency of 0.01Hz to 10 6HZ, with an amplitude of 5 mV, and the ionic conductivity of the sample was calculated.

[0195] 6. Lithium-ion battery energy density and cycle life test

[0196] The cycle test temperature is 25°C. The battery is charged at a constant current of 3C to the upper limit voltage, and then charged at a constant voltage to 0.05C. After standing for 5 minutes, it is discharged at 0.33C to the lower limit voltage. The capacity obtained in this step is the initial capacity. The capacity is multiplied by the average discharge voltage and then divided by the cell volume to obtain the energy density. A 3C charge / 0.33C discharge cycle test is performed until the capacity decays to 80% SOH, and the corresponding number of cycles is recorded to obtain the corresponding life data.

[0197] 7. Battery expansion force test

[0198] Before test 7, the battery is fixed in the clamp of the pressure sensor and clamped with a fixed pressure. Capacity calibration and cycle testing are performed according to the process in test 7. The expansion force change is monitored during the cycle. The ratio of the expansion force increment when the capacity decays to 80% to the initial expansion force is the expansion force change.

[0199] Table 2 shows the negative electrode active materials and battery performance test results of Examples 1 to 30 and Comparative Example 1.

[0200] Table 1

[0201]

[0202]

[0203] Table 2

[0204]

[0205]

[0206] By comparing the examples and comparative examples, it can be seen that the composite negative electrode material obtained by arranging a silicon material layer on the surface of a carbon fiber composite material having a three-dimensional fiber network structure can reduce the expansion force of the battery, improve the ionic conductivity of the lithium-ion battery and the cycle life at high rates. By controlling the relevant condition parameters in the preparation process of the negative electrode active material, the various properties of the negative electrode sheet and the lithium-ion battery can be adjusted, so that a lithium-ion battery with better comprehensive performance can be obtained according to actual application requirements.

[0207] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A composite negative electrode material, characterized in that: The invention comprises a carbon fiber composite material and a silicon material layer arranged on at least a part of the surface of the carbon fiber composite material, wherein the carbon fiber composite material comprises carbon fibers with a three-dimensional fiber network structure and a fast ion conductor composited on the carbon fibers.

2. The composite negative electrode material according to claim 1, characterized in that: The fast ion conductor includes one or more of a perovskite fast ion conductor, a garnet fast ion conductor and a NASICON fast ion conductor; Optionally, the fast ion conductor includes a perovskite fast ion conductor, a garnet fast ion conductor and a NASICON fast ion conductor; Further optionally, the mass ratio of the perovskite type fast ion conductor, the garnet type fast ion conductor and the NASICON type fast ion conductor is (1-2):(1-2):

1.

3. The composite negative electrode material according to claim 2, characterized in that: The chemical formula of the perovskite fast ion conductor is Li 3x1 La 2 / 3-x1 M y1 TiD z1 O3, where M includes Ba 2+ and Sr 2+ One or more of, D includes Al 3+ and Zr 4+ One or more of 0.04≤x1≤0.167, 0≤y1≤1, 0≤z1≤1, optional Li 0.33 La 0.56 TiO3; and / or, The chemical formula of the garnet-type fast ion conductor is Li 7-y2 La 3-x2 A x2 Zr 2-y2 B y2 O 12 , wherein 0≤x2≤3, 0≤y2≤2, A includes one or more of Y, Nd and Gd, B includes one or more of Nb and Ta, and can be selected from Li7La3Zr2O 12 and / or, The chemical formula of the NASICON type fast ion conductor is Li 1+x3 M'2(PO4)3, M' includes one or more of Al, Ti, Ge, Hf, 0.1≤x3≤0.5, and can be Li 1.3 Al 0.3 Ti 1.7 (PO4)3.

4. The composite negative electrode material according to any one of claims 1 to 3, characterized in that: The fast ion conductor is ceramic particles, and the average volume particle size Dv50 of the ceramic particles is 10nm to 70nm, and can be optionally 20nm to 50nm.

5. The composite negative electrode material according to any one of claims 1 to 3, characterized in that: The carbon fiber composite material satisfies at least one of the following characteristics (1)-(3): (1) The average diameter of the carbon fibers in the carbon fiber composite material is 0.1 μm to 1 μm; (2) The porosity of the carbon fiber composite material is 20% to 70%; (3) The mass ratio of carbon fiber to fast ion conductor in the carbon fiber composite material is (1-19):1, and can be optionally (1.2-9):

1.

6. The composite negative electrode material according to any one of claims 1 to 3, characterized in that: The silicon material layer satisfies at least one of the following characteristics (4)-(5): (4) The thickness of the silicon material layer is 5 nm to 100 nm, and can be optionally 10 nm to 80 nm; (5) The average volume particle size Dv50 of the silicon material in the silicon material layer is 3 nm to 10 nm.

7. The composite negative electrode material according to any one of claims 1 to 3, characterized in that: The composite negative electrode material satisfies at least one of the following characteristics (6)-(10): (6) The average volume particle size Dv50 of the composite negative electrode material is 5 μm to 20 μm; (7) The specific surface area of ​​the composite negative electrode material is 1 m 2 / g~20m 2 / g; (8) Based on the mass of the composite negative electrode material, the mass content of the silicon material in the silicon material layer is 1% to 70%; (9) Based on the mass of the composite negative electrode material, the mass content of the fast ion conductor is 10% to 50%; (10) Based on the mass of the composite negative electrode material, the mass content of the carbon fiber is 5% to 30%.

8. A method for preparing a composite negative electrode material according to any one of claims 1 to 7, characterized in that: include: Providing the carbon fiber composite material; The silicon material layer is formed on the carbon fiber composite material.

9. The method for preparing a composite negative electrode material according to claim 8, characterized in that: The method for preparing the carbon fiber composite material comprises the following steps: S11, mixing an organic polymer, a fast ion conductor, a complexing agent and a solvent to obtain a mixed solution; S12, heat-treating the mixed solution to obtain a fiber prefabricated solution; S13, preparing the fiber prefabricated liquid through an electrostatic spinning process to obtain a fiber structure material; S14, sintering the fiber structure material to obtain a carbon fiber composite material.

10. The method for preparing a composite negative electrode material according to claim 9, characterized in that: The organic polymer includes one or more of polyvinyl alcohol, polyacrylonitrile, polyethylene oxide, polyphenylene ether, polyethylene glycol, polymethyl methacrylate and polyvinylidene fluoride hexafluoropropylene.

11. The method for preparing a composite negative electrode material according to claim 10, characterized in that: Satisfies at least one of the following characteristics (11)-(12): (11) The concentration of the organic polymer in the mixed solution is 0.01 to 0.20 Kg / L, and can be 0.08 to 0.18 Kg / L; and / or, (12) The concentration of the fast ion conductor is 0.01 to 0.20 Kg / L, and can be optionally 0.08 to 0.15 Kg / L.

12. The method for preparing a composite negative electrode material according to any one of claims 8 to 11, characterized in that: The method for forming the silicon material layer includes at least one of chemical vapor deposition, physical vapor deposition, plasma spraying and screen printing, and chemical vapor deposition can be selected.

13. A negative electrode plate, characterized in that: The invention comprises the composite negative electrode material according to any one of claims 1 to 7 or the composite negative electrode material prepared according to the method according to any one of claims 8 to 12.

14. A secondary battery, characterized in that: Including the negative electrode sheet as described in claim 13.

15. An electrical device, characterized in that: Includes the secondary battery as claimed in claim 14.

Citation Information

Patent Citations

  • Negative electrode material for non-aqueous electrolyte secondary battery and preparation method thereof

    CN114068887A

  • Fast ion conductor coated silicon-carbon composite material and preparation method thereof

    CN114824237A

  • Negative pole piece and preparation method thereof, secondary battery, battery module, battery pack and power utilization device

    CN115832242A

  • Silicon composite nanofiber, silicon composite nanofiber membrane and preparation method and application of silicon composite nanofiber membrane

    CN115966658A

  • Negative electrode material for nonaqueous electrolyte secondary battery, and preparation method therefor

    WO2022021933A1